2007
DOI: 10.1029/2007gl031438
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between earthquakes and volcano activity

Abstract: [1] Using the 1973-2005 worldwide catalogues for M ! 4.8 seismicity and VEI ! 0 volcano eruptions, we find a significant, when tested against catalogue randomizations, increase of eruption onsets on the earthquake day. This result emerges from stacking time series of daily eruption rates relatively to earthquake time, t 0 , over the whole seismicity catalogue. It is stronger for earthquake-volcano pairs for which the volcano is within ten rupture size from the epicenter. These results show that M ! 4.8 À VEI !… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 15 publications
(35 reference statements)
3
41
0
Order By: Relevance
“…Darwin, 1840). Earthquake and eruption catalogs provide statistical support for the occurrence of long-distance triggering; both Linde and Sacks (1998) and Lemarchand and Grasso (2007) found that volcanic eruptions occur more frequently in the few days following large earthquakes. Reviews of proposed mechanisms for short-term dynamic triggering of volcanic eruptions are given by Hill et al (2002) and Manga and Brodsky (2006).…”
Section: Volcanoesmentioning
confidence: 93%
See 1 more Smart Citation
“…Darwin, 1840). Earthquake and eruption catalogs provide statistical support for the occurrence of long-distance triggering; both Linde and Sacks (1998) and Lemarchand and Grasso (2007) found that volcanic eruptions occur more frequently in the few days following large earthquakes. Reviews of proposed mechanisms for short-term dynamic triggering of volcanic eruptions are given by Hill et al (2002) and Manga and Brodsky (2006).…”
Section: Volcanoesmentioning
confidence: 93%
“…The ongoing eruption, now known as ''Lusi'', covers an area of 6.5 km 2 and has displaced tens of Lemarchand and Grasso (2007), Manga and Brodsky (2006), Mellors et al (2007), Montgomery and Manga (2003), Wang et al (2006) with additional mud volcanoes eruptions reported in Delisle (2005), Snead (1964), Ambraseys and Bilham (2003), Deville (submitted for publication), Bonini (submitted for publication) and Rukavickova and Hanzl (2008). The solid and dotted lines are the empirical liquefaction limit and error, respectively, determined by Wang et al (2006).…”
Section: Lusimentioning
confidence: 96%
“…600 houses and affected more than 6000 persons despite its moderate strength. Lemarchand and Grasso (2007) showed that moderate earthquakes of magnitude M P 4.8 are capable of triggering eruptions at volcanoes within a distance from the earthquake less than ten times the fault length. Although the chance of such an earthquake-eruption interaction is small (0.3%), it is not unlikely to occur in this study area which shows strong volcano-tectonic interactions.…”
Section: Significance Of Tectonic Control For Volcanic Activity and Fmentioning
confidence: 98%
“…where q is density, and T i and v i are the period and particle velocity of the ith mode, and the sum is taken over all Lemarchand & Grasso (2007) modes for ground motion. For an earthquake of magnitude M, the seismic energy density e at a distance r from the earthquake source may be estimated from the empirical relation (Wang 2007) log r ¼ 0:48M À 0:33 log e À 1:4; ð2Þ where r is in km and e in J m )3 .…”
Section: The Seismic Energy Density: a General Metricmentioning
confidence: 99%